Coherent nuclear motions and exciton state dynamics in photosynthetic light-harvesting pigments - Pullerits, T.; Chachisvilis, M.; Jones, M. R.; Hunter, C. N.; Sundstrom, V. (1994 5th European Quantum Electronics Conference, Amsterdam, Netherlands, 1994-08-28 - 1994-09-02, 1994)
Coherent nuclear oscillations in two intact photosynthetic light-harvesting pigments were observed for the first time using the approx. 40-fs tunable pulses from a mode-locked Ti:Sa laser. Furthermore, steady-state optical spectroscopy and theoretical calculations provide evidence that exciton states are present in the pigments. The possible antenna configurations that would give rise to the observed excited-state absorption and polarization were investigated.